D2‐like dopamine receptors mediate regulation of pupal diapause in Chinese oak silkmoth Antheraea pernyi. Issue 2 (26th June 2014) - Wang, Qiushi; Hanatani, Ikumi; Takeda, Makio; Oishi, Katsutaka; Sakamoto, Katsuhiko
Abstract The present study investigated the pharmacological properties of dopamine receptors that functioned in the termination of pupal diapause in the Chinese oak silkmoth, Antheraea pernyi (Lepidoptera: Saturniidae). Dopamine receptors are classified according to their structure and function into two subfamilies as D1‐ and D2‐like receptors. D1‐like receptors activate, whereas D2‐like receptors inhibit, adenylate cyclase. We examined the effects of agonists and antagonists selective for D1‐ and D2‐like receptors on the diapause state. As A. pernyi is a long‐day species, pupal diapause is maintained during short days and can be terminated by exposure to a long‐day photoperiod. The D2‐like receptor‐selective agonist quinpirole delayed the timing of adult emergence under long days, and the D2‐receptor‐selective antagonist sulpiride terminated pupal diapause even under a short‐day photoperiod. The D1‐like receptor‐selective agonist and antagonist, SKF‐38393 and SCH‐23390, respectively, caused no significant effects on diapause pupae. These results suggest that not D1‐ but D2‐like receptors mediated diapause regulation in A. pernyi. This dopamine pathway appeared to block the termination of pupal diapause. Furthermore, the actions of the cAMP analog 8‐CPT‐cAMP and dopamine receptor antagonists upon diapause pupae were similar, which supports the notion that D2‐like receptors involved in diapause of this insect prevent adenylate cyclase from producing cAMP like vertebrate D2‐like receptors. Taken together, our findings suggest that dopamine blocked diapause termination through D2‐like receptors that inhibited adenylate cyclase in A. pernyi. During short days under which diapause was maintained in pupae, the dopaminergic mechanism might be stimulated to suppress cAMP levels in cells regulating diapause.